If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1.3(j + -5) = -5.2 Reorder the terms: -1.3(-5 + j) = -5.2 (-5 * -1.3 + j * -1.3) = -5.2 (6.5 + -1.3j) = -5.2 Solving 6.5 + -1.3j = -5.2 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-6.5' to each side of the equation. 6.5 + -6.5 + -1.3j = -5.2 + -6.5 Combine like terms: 6.5 + -6.5 = 0.0 0.0 + -1.3j = -5.2 + -6.5 -1.3j = -5.2 + -6.5 Combine like terms: -5.2 + -6.5 = -11.7 -1.3j = -11.7 Divide each side by '-1.3'. j = 9 Simplifying j = 9
| 8d-14=7+d | | 10x+22=128 | | 2.5(d-4)=7.5 | | D(t)=-200t+9000 | | 3n+7=7n-13 | | -5(3x-5)=2(X-6)-31 | | xy-y-x=-31 | | 3(k+2)=12 | | X^2-6k-7=0 | | -11(c-832)=-968 | | 4x-z= | | 2=3m-4 | | 1050y+200x=2 | | -6(u+7)=3u+48 | | 45+5f=-45 | | 4(2x+1)=34 | | xy+y+x=-41 | | y=150-2.5x | | (X-10)=9+4x | | 2x-25x-25=0 | | 12xy/8 | | 4(x+12)+19=-89 | | 3t-2=3t-3 | | -8=-6+-2q | | -9/2x-8/7=-7/5 | | 6x-1=2x-29 | | 15d-7=38 | | 3+2b=-11 | | a=1/4 | | d/3-1=1 | | 4R-4R-4=3R+10 | | 4+2d=20 |